2011
DOI: 10.1007/s13593-011-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial management practices and mitigation of greenhouse gas emissions in the agriculture of the Canadian Prairie: a review

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…Other studies examining pasture management intensification (Asgedom and Kebreab, 2011;Bell et al, 2012b;Foley et al, 2011) also reported this relationship. Pasture yield and forage quality are dependent on precipitation patterns.…”
Section: Pasture Management Cow-calf Efficiency and Whole-system Susmentioning
confidence: 61%
“…Other studies examining pasture management intensification (Asgedom and Kebreab, 2011;Bell et al, 2012b;Foley et al, 2011) also reported this relationship. Pasture yield and forage quality are dependent on precipitation patterns.…”
Section: Pasture Management Cow-calf Efficiency and Whole-system Susmentioning
confidence: 61%
“…Increasing N fertilizer application for the sake of providing sufficient quantity of grains to meet the ever-growing population's needs has given rise to heavy carbon emissions. A well consideration of applying the N fertilizer at right rate, proper selection of the N sources, and timing application is highly recommended (Asgedom and Kebreab 2011). Cropping system is the major component of farmland, by managing farm in space and time.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cropping intensification is recognized as a key farming strategy in reducing global warming potential (Gan et al 2012). The adoption of intercropping has significant advantages on carbon sequestration than conventional sole cropping (Asgedom and Kebreab 2011;Gan et al 2011a). For example, maize-soybean (Glycine max L.) intercropping (Dyer et al 2012) and maize-wheat intercropping (Beedy et al 2010) enhance soil carbon sequestration and reduce carbon emission significantly compared to the corresponding monocultures.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the cattle industry plays an essential role in the Canadian economy, generating more than $7.3B in cash farm sales in 2011 (www5.statcan.gc.ca/cansim/a47, Table 0020065 Farm Financial Survey, Financial Structure by Farm Type, Average per Farm, accessed December 2014), much of it benefitting rural communities. In order to manage these contrasting attributes and to inform government policy (Asgedom and Kebreab 2011), it is important to document the current husbandry practices used in beef cattle operations and to document changes that have occurred over time. The last targeted, extensive farm survey of beef cattle husbandry in Canada, the Livestock Farm Practices Survey (LFPS), was completed in 2006 (Sheppard et al 2009;Sheppard and Bittman 2012), with a more limited survey of the sale and consumption of pasture-finished beef being conducted in 2005 (Lozier et al 2005).…”
Section: Mots Clé Smentioning
confidence: 99%